House feeding system improves the estrus rate in yaks (Bos grunniens) by increasing specific fecal microbiota and myo-inositol content in serum - Zhu, Yanbin; Li, Xin; zhaxi, Lousang; zhaxi, Suolang; Suolang; Ciyang; Sun, Guangming; yangji, Cidan; wangdui, Basang (Frontiers in Microbiology, 2022)
Yaks (Bos grunniens) of grazing widely exist lower fertility, this situation severely limited the income for local pastoralists. However, we have recently found that the estrus rate of yak in house feeding (HF) was improved by 52% compared to grazing (G). To explain this phenomenon, we used gas chromatography-mass spectrometry and 16S rRNA gene sequencing to analyze the serum metabolites and fecal microbiota of rutting yaks under grazing and house feeding system, respectively. The results showed that 73 metabolites were significantly different (p < 0.05 and VIP > 1) between G and HF system in the total 304 metabolites quantified. Of these differential metabolites, 53 metabolites were up-regulated and 20 metabolites were down-regulated in HF system compared with G system. The majority of differential metabolites were Organic oxygen compounds, Organic acids and derivatives, and Lipids and lipid-like molecules. KEGG pathway mapper indicated that 25 metabolic signaling pathways were significantly different among two system. We found top 3 pathways which these enriched including Central carbon metabolism in cancer, Aminoacyl−tRNA biosynthesis, and ABC transporters. 16S rRNA gene sequencing data showed that there was no significant different in Chao 1 index among two system. The PCA indicated that HF system and G system were distinctly clustered separately in distribution of fecal microbiota. The G system showed significantly higher abundances of Firmicutes. The HF system showed significantly higher abundances of Alistipes, Treponema, and Rikenellaceae_RC9_gut_group. Pearson’s correlation analysis and core network analysis results showed that Rikenellaceae_RC9_gut_group, Alistipes, and Treponema significantly positive correlation with Myo-inosito, and they were also the core bacteria. In summary, house feeding system promoted the estrus rate, changed composition of fecal microbiota and serum metabolites of yaks. It was possible that the increased estrus rate may be due to the enhanced Myo-inositol content in serum of yaks via house feeding system. Correlation analysis implied that it may also be partly increase Myo-inositol content via the specific fecal microbiota of yaks, further contributing to the estrus rate. The findings of the present study may provide a novel therapeutic strategy for the low estrus rate of grazing yaks.